Development of a New Curriculum in a Positive Youth Development Program: The Project P.A.T.H.S. in Hong Kong - Daniel T. L. Shek; Hing Keung Ma; Rachel C. F. Sun (The Scientific World Journal)
The design of a new curriculum in a positive youth development program (Project P.A.T.H.S.) in Hong Kong is outlined. The Tier 1 Program of the original phase of the Project P.A.T.H.S. is a universal positive youth development program for students in Secondary 1 to Secondary 3 with the curricula developed by a research team comprising scholars in different disciplines (e.g., social work, psychology, and education). The 120 teaching units are designed with reference to 15 positive youth development constructs identified in the successful positive youth development programs. In the extension phase of the project, a new curriculum with 60 teaching units is developed in accordance with these 15 constructs with specific reference to five major adolescent developmental issues. These issues include substance abuse, sexuality issue, Internet addiction, bullying, and money and success issues. The principles underlying the program development and implementation strategies are outlined.